Nanodiamonds carrying silicon-vacancy quantum emitters with almost lifetime-limited linewidths - Uwe Jantzen; Andrea B Kurz; Daniel S Rudnicki; Clemens Schäfermeier; Kay D Jahnke; Ulrik L Andersen; Valery A Davydov; Viatcheslav N Agafonov; Alexander Kubanek; Lachlan J Rogers; Fedor Jelezko (New Journal of Physics, 2016)
Colour centres in nanodiamonds are an important resource for applications in quantum sensing, biological imaging, and quantum optics. Here we report unprecedented narrow optical transitions for individual colour centres in nanodiamonds smaller than 200 nm. This demonstration has been achieved using the negatively charged silicon vacancy centre, which has recently received considerable attention due to its superb optical properties in bulk diamond. We have measured an ensemble of silicon-vacancy centres across numerous nanodiamonds to have an inhomogeneous distribution of 1.05 nm at 5 K. Individual spectral lines as narrower than 360 MHz were measured in photoluminescence excitation, and correcting for apparent spectral diffusion yielded an homogeneous linewidth of about 200 MHz which is close to the lifetime limit. These results indicate the high crystalline quality achieved in these nanodiamond samples, and advance the applicability of nanodiamond-hosted colour centres for quantum optics applications.